British America - Archer, J. (Contributor); Hughes, William (Cartographer) (William Mackenzie, 1870)
Map of British America including Canada, First Nations' territories with Anglo/Franco names, British Columbia, Rupert's Land, U.S. Alaska, mainland United States, Greenland and Iceland. Shows elevation, lakes, waterways, factories, forts, and other details. "Comparative lengths of England and British & Russian America: England 350 Miles - Area 58,000, British & Russian America 3950 Miles - Area 3,300,000" Scale approximately 1 inch to 300 English miles. Relief shown by hachures. Manitoba, P.E.I, Alberta, Saskatchawan, Vancouver Island, Newfoundland, Rupert's Land not part of Canada. Drawn and engraved by J. Archer, Pentonville, London. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . The new comprehensive atlas of modern geography : with an introduction to physical and historical geography, and an alphabetical index of the latitudes and longitudes of 70,000 places Lake Nippissing an inaccurate blob.